“I should have liked to be called Prince de Monbart”: On the Problem of Identifying the Reference - Tatyana V. Kovalevskaya (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
The article considers a series of possible allusions implied by the name of “prince de Montbard” in Captain Lebyadkin’s monolog in The Devils. The article analyzes the traditional reference to the allegedly historical figure of the buccaneer Monbars (or Montbars) presumably featured in several adventure novels. We point out that the buccaneer Montbars probably never existed; we consider the novel by Jean-Baptiste Picquenard traditionally cited as a work about the historical Montbars and several novels by Gustave Aimard (published in Russian translations by the time Dostoevsky started working on The Devils). In all those novels, the hero called Montbars is either unrelated to the alleged prototype or is given a fictional biography. The literary allusion to Montbars is important both as an assertion of Lebyadkin’s Romantic ambitions and as an indication of his social ambitions and his dissatisfaction with his own personality that he would like to replace with another’s, for which purpose he aptly selects a provisionally real Montbars. The article also considers a possible historical allusion to André de Montbard, one of the founders of the Order of the Temple. This allusion is connected to the accusations against the Knights Templar who had been charged with apostasy. The article also considers the meaning of the title “prince” and its political and religious connotations that go far beyond romantic adventure-seeking. The ultimate conclusion is that it is hardly possible and necessary to determine some singular and unequivocal literary or historical reference. The range of meanings implied by the name of “prince de Montbard” generally fits in the overall concept of The Devils as a novel about metaphysical imposture that includes the comical Captain Lebyadkin among potential impostors.